1987
DOI: 10.1099/00221287-133-4-835
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the Aerobactin Iron Uptake System Among Escherichia coli Isolates From Infections of Farm Animals

Abstract: To assess the importance of aerobactin-mediated iron uptake as a bacterial virulence determinant in animal infections, a total of 576 strains of Escherichia coli isolated from cattle, chickens, sheep and pigs were screened by colony hybridization to determine the presence of the aerobactin genetic determinants, and by a bioassay to detect aerobactin secretion in iron-limited conditions. Results obtained by the two complementary methods correlated well. The incidence of the aerobactin system was very high among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 15 publications
1
34
0
2
Order By: Relevance
“…The presence of operon aerobactin is in general related to ColV plasmids, although it can be chromosomal (Linggood et al 1987, Johnson 1991. Table 2 shows that iut A gene, which codifies outer membrane protein aerobactin receptor, was detected in 45.8% of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of operon aerobactin is in general related to ColV plasmids, although it can be chromosomal (Linggood et al 1987, Johnson 1991. Table 2 shows that iut A gene, which codifies outer membrane protein aerobactin receptor, was detected in 45.8% of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Possession of the aerobactin system by pathogenic bacteria has been implicated as a virulence factor by epidemiological evidence (Montgomerie et al, 1984;Carbonetti et al, 1986;Linggood et al, 1987;Jacobson et al, 1988) and by studies using laboratory strains in experimental infections (Williams, 1979). We believe, however, that this paper contains the first report in which the aerobactin genes alone, isolated from other potential virulence factors encoded, for example, by ColV plasmids, have been studied in the genetic background of a clinical E. coli isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli (O'Brien & Gibson, 1970) and other members of the Enterobacteriaceae (Pollock et al, 1970;Perry & San Clemente, 1979) synthesize the phenolic siderophore enterochelin (enterobactin), but some clinical isolates of enteric bacteria also possess a second high-affinity iron-uptake system mediated by the hydroxamate siderophore aerobactin (Braun, 1981 ;Warner et al, 1981 ;Roberts et al, 19866;Martinez et al, 1987). The ability to make and use aerobactin increased the virulence of E. coli K12 strains in experimental infections (Williams, 1979), and a number of epidemiological studies showed significantly higher incidence of the aerobactin system among bacteria isolated from extraintestinal infections than among isolates from the faeces of healthy individuals (Montgomerie et al, 1984;Carbonetti et al, 1986;Linggood et al, 1987;Jacobson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…An early study conducted on one-day-old chickens suggested a positive association between low iron levels, APEC survival and the pathogenicity of the tested APEC strains (Lafont et al, 1987). Furthermore, several studies have suggested that the expression of an iron acquisition system occurs mainly in APEC compared with AFEC (Dias da Silveira et al, 2002;Dozois et al, 1992;Emery et al, 1992;Linggood et al, 1987). Among APEC strains, iron acquisition systems can be encoded by genes located on plasmids (Sabri et al, 2008;Skyberg et al, 2006) or by chromosomal PAIs (Kariyawasam et al, 2006a).…”
Section: Iron Acquisition Mechanismsmentioning
confidence: 99%
“…Previous studies have indicated that the aerobactin system is found in more than 72% of APEC isolates (Emery et al, 1992;Linggood et al, 1987). The aerobactin iron acquisition system consists of hydroxamate siderophore aerobactin and ferric aerobactin uptake proteins, which are encoded by iucA and iucC genes that are located on ColV plasmids (Boerlin and White, 2013).…”
Section: Iron Acquisition Mechanismsmentioning
confidence: 99%